Effect of Particle Size and Citric Acid Concentration on the Yield and pH of Butterfly Flower (Clitoria ternatea L.) Extract - Cahyono, Nilam; Kasim, Anwar; Dewi, Kurnia Harlina (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
This research aimed to determine the effect of differences in butterfly pea flower particle size and citric acid concentration on butterfly pea flower extraction, including yield and pH value analysis. The results showed that the particle size of butterfly pea flowers and the concentration of citric acid affected the yield. pH analysis showed that only treatments with different concentrations of citric acid affected the pH of butterfly pea flower extract. The highest yield in the treatment (7.52) and the highest pH (4,74). The above treatment can only be used for acidic food products, and citric acid can be replaced with food additives that lower the pH value but do not affect the taste so that it can be applied to all types of food.